(untitled) (Research, Society and Development, 2022)
The field of teaching and learning for the development of knowledge is a constant movement of discursive practices about the relationships between subjects for the training process by the problematizing bias of new learning, perceived for the present research, the discipline of Libras, in the condition of second tongue. Concatenating with the theme, the objective of the research is to analyze the offer of Libras as a second language for listeners in the Licentiate courses of Higher Education Institutions in Rio Grande do Sul. The exploratory research surrounds the treatment of access to the teaching plans of HEI institutions, totaling 24 Institutions. The data were evidenced from the construction of a cataloged table and later analyzed. For the debate of results and discussions, the discipline of Libras has to be practical, but as Libras also encompasses culture, history and permeates the life of a people, making it necessary to deepen the relevant theoretical knowledge of language and its interactions pedagogical practices, whether in the theoretical and practical fields, thus providing opportunities for students to build knowledge about the way of life of the deaf, their practices and the social development of collective experiences in education.